B‐cell modulation with anti‐CD79b antibodies ameliorates experimental autoimmune encephalitis in mice. Issue 4 (11th January 2022) - Renner, Kerstin; Neumayer, Sophia; Talke, Yvonne; Buchtler, Simone; Schmidbauer, Kathrin; Nimmerjahn, Falk; Lux, Anja; Winter, Frederike; Salewski, Jan‐Nicklas; Mack, Matthias
Abstract: B cells play a major role in the pathogenesis of many autoimmune diseases like MS, rheumatoid arthritis, or systemic lupus erythematosus. Depletion of B cells with anti‐CD20 antibodies is an established therapy for MS. However, total B‐cell depletion will also affect regulatory B cells that are known to suppress autoimmune responses. In our studies, we describe an alternative approach based on targeting CD79b that induces only partial B‐cell depletion and achieves therapeutic effects by B‐cell modulation. Prophylactic and therapeutic treatment with an antibody against CD79b and also a deglycosylated variant of this antibody, lacking effector function like antibody‐dependent cellular cytotoxicity or complement activation, significantly reduced the development and progression of EAE in mice. Our data show that modulation of B cells via CD79b is equally effective as almost complete B‐cell depletion with anti‐CD20 antibodies and may constitute an alternative approach to treat MS. Abstract : B cell modulation with anti‐CD79b has multiple downstream effects including less cerebral leukocyte infiltration, changed cytokine release, lower MOG‐specific antibodies and lower MOG‐specific T cell proliferation. All of these effects contribute to amelioration of experimental autoimmune encephalitis.